Pemahaman Akidah Islam dan Pengamalan Ibadah Masyarakat di Desa Bonto Masunggu Kabupaten Bone - Muh Ashabul Kahfi; Ahmad Abdullah; Ahmad Nashir (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
The level of depth of Aqidah in the people of Bonto Masunggu Village, Bone Regency is stated to be in the good category, proven by the people who believe in the existence of Allah and they do not worship except Allah, they have carried out Allah's commands and avoided all prohibitions, so that in the process of cultivating the depth of Aqidah in the community declared good. Its understanding in the form of prayer can be seen in the following explanation 1) Many people understand the statement regarding the understanding of worship in the form of prayer because they understand its implementation well so they always carry out prayers in congregation in the mosque. 2) Most people who understand worship in the form of prayer understand it because there is guidance and guidance regarding the proper implementation of prayer. 3) The community's statement regarding the understanding of worship in the form of prayer no longer lacks understanding and does not understand at all because there are no people in Uru Hamlet who do not perform prayer services. In general, they understand the teachings of the Islamic religion well and thank God, thanks to the progress of the people there, they have or always practice the teachings of Islam and these people practice the teachings of the Islamic religion in society by carrying out all the commands of Allah SWT. This research aims to determine the understanding of the Aqidah and practice of worship of the people of Bonto Masunggu Village, Bone Regency. The type of research used in this research is descriptive qualitative research. By using observation guide instruments, interview guidelines and documentation notes. The data analysis techniques used are data reduction, data display and conclusion drawing.